ANALISIS SWOT PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) SENTRA INDUSTRI OLAHAN KEDELAI DI DESA SELAT KECAMATAN PEMAYUNG KABUPATEN BATANGHARI - Siti rapi’ah; Maulana Yusuf; Yuliana Safitri (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research discusses SWOT analysis of micro, small and medium enterprises (MSMEs) soybean processing industry centers in Selat Village, District. Pemayung Kab. Batang Hari. The formulation of the problem in this research is to find out what the strengths, weaknesses, opportunities and threats are in the soybean processing industry center business. This research aims to find out what the strengths, weaknesses, opportunities and threats are in the soybean processing industrial center business. To obtain data, the author used descriptive qualitative research, namely research with the aim of checking certain symptoms that occur in the field. There are two sources of data used in this research, namely primary and secondary data. Primary data sources are the results of interviews conducted by authors and business owners and secondary data are documentation, books and also the internet. The research results show that the soybean processing industry center has implemented a SWOT analysis to determine strengths, opportunities and minimize weaknesses and threats.